DESIGNING READING MATERIAL BASED ON LOCAL CULTURAL CONTENT FOR YEAR-8 STUDENTS OF PUBLIC JUNIOR HIGH SCHOOLS - Denuk Ayu Aditya; Clarry Sada; Dwi Riyanti (Journal of English Educational Study (JEES), 2023)
Communication occurs in contexts that cannot be separated from culture. Therefore, it can be claimed that culture needs to be included in language teaching and learning. The cultural content of the teaching materials then plays an important role in how culture is presented in EFL contexts, especially in textbooks. In the first of the study, we create a list of criteria from students how some class consists of several students who have different backgrounds where culture are included; religion, ethnicity, gender, and age for the analysis of cultural content in English textbooks based on student's perception and evaluation of the cultural content in textbooks. The researcher then selected a media used in junior high school to determine to what extent local cultural content is integrated into junior English textbooks and find the evaluation result of the media designed.